(untitled) (Indian Journal of Animal Production and Management, 2013)
In an outbreak of foot and mouth disease (FMD) in an organized farm, out of 657 pigs, 534 (81.28 %) animals were affected and 17 died. The disease was confirmed as FMD by Sandwich ELISA and serotype A of FMD virus was identified. By adopting scientific managemental practices mortality rate could be restricted to 2.5 per cent. Of the 17 dead animals, 15 animals were below 6 months and 2 were above 8 months of age. Higher case fatality was recorded in the young animals which might be due to lack of immunity and maturity of the immune system. Vaccination of pigs with cattle FMD vaccine was not found to be useful.